The World Needs the Wonder You See - Gaines, Joanna, 1978-; Swaney, Julianna; Magnolia Publications (Nashville, Tennessee : Tommy Nelson, an imprint of Thomas Nelson, 2025)
"Bestselling author and Magnolia cofounder Joanna Gaines welcomes you on an imaginative adventure through nature's small surprises and invites you and your kids to be curious, slow down, and take in everyday wonders. With vibrant art by Julianna Swaney, The World Needs the Wonder You See will inspire your family to press pause and explore together."--
Keywords: Nature -- Juvenile fiction; Wonder -- Juvenile fiction; Nature -- Fiction; Wonder -- Fiction; Stories in rhyme; Picture books